KAJIAN KEMAMPUAN TANAH DALAM MENAHAN AIR PADA TIGA SATUAN PENGGUNAAN LAHAN DI DESA KARANGPATIHAN KECAMATAN BALONG KABUPATEN PONOROGO - Diah Rahmadani; Purnomo Edi Sasongko; Kemal Wijaya (BPFP Universitas Bengkulu, 2023)
[PREDICTION OF SOIL WATER HOLDING CAPACITY FOR DIFFERENT TYPES OF LAND USE IN KARANGPATIHAN VILLAGE, BALONG SUBDISTRICT, PONOROGO DISTRICT USING AVAILABLE SOIL CHARACTERISTICS]. Water has significant roles for plant growth and development. The ability of soil in various types of land use to hold water is influenced by their physical and chemical properties. Meanwhile, land use types in Karangpatihan village are dominated by dry land, rice fields, and bushes. Therefore, the aim of this study was to predict soil water holding ability (WHC) in three different land use type in Karangpatihan village using available soil characteristics. Samples of disturbed and undisturbed soil in each land use type were collected with four replicates using purposive random sampling to determine their physico-chemical characteristics. Data analysis was performed using correlation and regression analysis to relate the soil characteristics in each land uses with its WHC. The results showed that the bush land use type had the highest WHC. Irrespective of land use type, WHC of soil was in order influenced by organic matter, soil texture, soil bulk density, soil porosity, and soil permeability